E-MAWATIK: MAWARIS ELECTRONIC MODULE DEVELOPMENT BASED ON REALISTIC MATHEMATICS - Rini Agustini; Jumaita Nopriani Lubis; Masdelima Azizah Sormin; Rina Juliana; Safran Efendi Pasaribu; Nurul Arifah Zahra (Program Pascasarjana UIN Sumatera Utara, 2025)
The study of mawaris (Islamic inheritance law) is often considered complex due to the involvement of precise mathematical calculations. However, conventional teaching methods tend to be less engaging and difficult to understand, especially for the younger generation who are more familiar with technology. Therefore, the development of an electronic module based on realistic mathematics, such as e-Mawamatik, becomes highly important. This module not only facilitates the understanding of mawaris concepts through an applied mathematical approach but also leverages technology to enhance students' interest and engagement. This study aims to develop an e-Mawamatik module for teaching mawaris that integrates mathematical concepts to simplify the understanding and calculation of inheritance distribution. The module is designed to help students comprehend inheritance division according to Islamic law through concrete examples and digital simulations. In addition, e-Mawamatik seeks to increase learning interest, support independent learning.. The development of e-Mawamatik adopts a research and development (R&D) method, involving the stages of needs analysis, design, development, implementation, and evaluation. Furthermore, the module will be tested by students and experts to ensure the accuracy of its content and the effectiveness of the learning process. Evaluation is carried out through user feedback and continuous improvement to produce an optimal module. The media expert validation score was 88.3%, language expert validation 87.5%, and material expert validation 90% and matematic realistic expert validation 87,5%, with an average score percentage categorized as very valid. The trial conducted by teachers and students of Grade XI at Madrasah Aliyah Pondok Pesantren K.H. Ahmad Dahlan Sipirok showed that respondents scored 85.10% for the needs and interest aspect, and 90.88% for the usage evaluation aspect. The average percentage score across all aspects was 88.6%, falling into the category of very valid.